Processos de luto em pessoas com HIV/AIDS: uma abordagem psicológica, social e teológica - Silva, Demétrio Félix Beltrão da (2013)
The research aims to address issues related to the processes experienced by a person living with HIV/AIDS, the emergence of grief and the need of an unprejudiced reception, the importance of religion and theology on this adaptive process so the person will be able to overcomewithin the standard suggested by the process of resilience. In this sense, the social role combined with psychological and theological issues appear as parameters that must be articulated so the stigmatization process can be increasingly redefinedthereby facilitating the search for meaning through faith, which can provide a permanent factor in their constructive process as a person. The attempt to explore the meaning of faith, respecting the truths of people living with the virus so that they can be accepted within the standards that suit their meanings.